Harmony or Discord? A Study on the Alignment Between National Objectives and Reformed Social Studies Textbooks in Egypt - Yehia, Lina (AUC Knowledge Fountain, 2025)
Education systems, in many parts of the world, have served as a channel for communicating national goals to students, and Egypt has not been an exception. This study examines how public textbooks effectively align with equipping future generations of Egyptians to fulfill the nation’s development policy goals set for 2030. Utilizing a qualitative research design, this study employed textbook and document analyses of the published national policy goals of the current administration, along with the most recently reformed social studies textbooks of Grades 4, 5, and 6, a product of EDU 2.0. Based on an analysis of national documents, the government intended values and skills required for future Egyptians to fulfill the nation's policy goals were identified and presented. Accordingly, these values and skills were used as textbook analysis criteria to evaluate the newly reformed social studies textbooks' contribution to fulfilling policy goals. The findings showed that the content of the newly reformed curriculum does indeed display alignment with the policies published and goals aspired, yet, it does that in a more external approach than a deeper-rooted one. Therefore, due to several limitations, it does not reach its full potential to foster skills and knowledge that can equip students to translate policy into effective implementation as envisioned. In conclusion, this study offers recommendations for future reforms to achieve national development objectives, arguing that social studies textbooks require more attention to the element of fostering skills to develop a generation capable of constructing a historical consciousness to be able to contribute effectively to society.